Continuation of a Tradition over Five Thousand Years: Lithic Assemblage from Loteshwar, North Gujarat, Western India - Gadekar, C.S.; Ajithprasad, P.; Madella, Marco; Balbo, Andrea; Rajesh, S.V.; Rondelli, B.; García-Granero Fos, Juan José; Rodríguez Antón, David; Yannitto, V. (University of Kerala, 2014)
Loteshwar (23 36' 1.8" N; 71 50' 11.8" E) is situated in the Sami Taluka of Patan District in North Gujarat, Western India. First excavated in 1990's the site was re-excavated by the North Gujarat Archaeological Project during November/December 2009. The 2009 excavation unearthed two cultural periods namely Mesolithic (dated between the end of the eighth millennium cal BC and the middle of síxth millennium cal BCE) and Ch.alcolithic (dated to around 3600-3000 BC). The comparative analysis of the lithic assemblages associated wíth. these periods is the main objective of the current study. Other artefacts and ecofacts recovered duríng the excavations suggest a changing economy at the site from hunting and gathering to agro-pastoralisam. However, the analysís of the lithic assemblage, in particular the cores show continuity in tenn of a tool technology (quartering technique of stone tool manufacturing) for over five thousand years. This technological continuity is assocíated to continuity in settlement patterns, characterized by the occupation of dune tops and the uninterrupted transmission of technological knowledge from one generation to another. Peer reviewed